Selection of Chilli Pepper (Capsicum frutescens L.) for Salinity Tolerance in Seed Germination - Marlina Mustafa; Yolanda Fitria Syahri; Mustafa Rauf (Universitas Sembilanbelas November Kolaka, 2019)
The obstacle of chilli pepper development in saline is that there is no salinity tolerant variety, so it is necessary to assemble tolerant varieties. Information on tolerant genotypes, selection criteria and determination of new selection methods at the germination level are needed to make it easier for breeders to select prospective tolerant varieties early. This study aims to determine tolerant genotypes, appropriate selection criteria and NaCl concentrations used for selection at the germination level. The study was arranged based on a completely randomized design with two factors: NaCl concentration and some chilli pepper genotypes. NaCl solution concentrations consist of five concentrations of N0: 0 g L-1 (EC 291 µS/cm, SAL 0,10), N1: 2 g L-1 (EC 3,71 ms/cm, SAL 2,0), N2: 4 g L-1(EC 6,60 mS/cm, SAL 3,60), N3: 6 g L-1 (EC 9,56 mS/cm, SAL 5,40) and N4: 8 g L-1 (EC 12,45 mS/cm SAL 5,40). The second factor is the genotype of chilli pepper consisting of 22 genotypes. The results showed that the most tolerant genotypes were G4, G7 and G15. Characters that can be used as selection criteria at the germination level are the percentage of germination, radical and hypocotyl length. The concentration of 8 g NaCl L-1 is effectively used to select tolerant genotypes